Research hotspots and trends of oculomotor nerve palsy from 2001 to 2021 based on web of science: A bibliometric analysis - Wang, Runze; Gao, Yang; Wu, ShanHong; Cai, Xiaojun; Yu, TianYang; Wang, Liyuan (Frontiers in Neurology, 2023)
Background: Oculomotor nerve palsy (ONP) is a clinically occurring neurological disorder. Due to the complex anatomy and long travel distances of the oculomotor nerve, the causes of ONP vary and manifest in various ways. With continued interest in this area, it has become necessary to conduct a bibliometric study in ONP. This work aims to synthesize and visually identify current research themes and future trends in ONP through a literature-based analysis. Method: Articles and reviews on ONP published from 2002 to 2021 were derived from the Web of Science Core Collection (WoSCC) database. We generated visual images and performed quantitative and qualitative analysis through an online bibliometric tool, Citespace and VOSviewer software. Results: A total of 1205 published articles were included in this analysis. The annual number of this area's publications is showing an overall upward trend, with the number of citations increasing every year, reaching 2698 by 2021. The United States (367) and Japan (116) dominated the list with the most numerous articles published. The University of California Los Angeles in the USA is the institution that published the highest number of articles (47). Engle EC (23) and the JOURNAL OF NEUROSURGERY (46) are the most influential authors and journals in this field. The co-occurrence network analysis divided the keywords into five main research themes, which mainly include clinical manifestations of ONP, aneurysms, cerebral neurological symptoms, diseases with ONP as a complication, and other neurological disorders. Conclusion: This study is the first comprehensive and systematic bibliometric analysis of the current state of global ONP research over the past 20 years. We organized current hotspots and expected trends and provided key information for exploring potential research frontiers in ONP.